2013
DOI: 10.3390/toxins5081422
|View full text |Cite
|
Sign up to set email alerts
|

Deletion and Gene Expression Analyses Define the Paxilline Biosynthetic Gene Cluster in Penicillium paxilli

Abstract: The indole-diterpene paxilline is an abundant secondary metabolite synthesized by Penicillium paxilli. In total, 21 genes have been identified at the PAX locus of which six have been previously confirmed to have a functional role in paxilline biosynthesis. A combination of bioinformatics, gene expression and targeted gene replacement analyses were used to define the boundaries of the PAX gene cluster. Targeted gene replacement identified seven genes, paxG, paxA, paxM, paxB, paxC, paxP and paxQ that were all re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(65 citation statements)
references
References 60 publications
0
65
0
Order By: Relevance
“…The function of the biosynthetic gene cluster for paxilline (179) has been investigated by gene deletion, complementation, and heterologous reconstitution experiments, which established the complete biosynthetic route of 179. 121,[128][129][130][131][132] In the paxilline pathway, indole-2-glycerol phosphate (192) serves as the indole donor, which is geranylgeranylated by the PTase PaxC to yield 3-geranylgeranylindole (193). The prenylation reaction differs from the above-described meroterpenoid pathways in two aspects.…”
Section: Biosynthesis Of Paxillinementioning
confidence: 99%
See 1 more Smart Citation
“…The function of the biosynthetic gene cluster for paxilline (179) has been investigated by gene deletion, complementation, and heterologous reconstitution experiments, which established the complete biosynthetic route of 179. 121,[128][129][130][131][132] In the paxilline pathway, indole-2-glycerol phosphate (192) serves as the indole donor, which is geranylgeranylated by the PTase PaxC to yield 3-geranylgeranylindole (193). The prenylation reaction differs from the above-described meroterpenoid pathways in two aspects.…”
Section: Biosynthesis Of Paxillinementioning
confidence: 99%
“…134 Furthermore, the involvement of paxA in paxilline biosynthesis is indicated, since the paxA-deletion mutant is unable to produce paxilline (179) and the deciency is complemented by the reintroduction of paxA. 132 PaxA is predicted to be a sixtransmembrane protein and is also present in the other indolediterpenoid biosynthetic gene clusters. However, reconstitution studies have revealed that paxA was not required for the production of 179, 131 and therefore the role of paxA remains enigmatic.…”
Section: Biosynthesis Of Paxillinementioning
confidence: 99%
“…Nine of these were putative orthologs of genes in the PAX cluster. All seven of the genes that are necessary for paxilline biosynthesis in P. paxilli [ paxG (geranygeranyl diphosphate synthase), paxA (integral membrane protein), paxM (FAD-dependent monooxygenase), paxB (integral membrane protein) paxC (prenyl transferase) paxP (cytochrome P450 monooxygenase) and paxQ (cytochrome P450 monooxygenase)], had homologs in the PEN cluster plus homologs of two genes [ paxD (aromatic prenyl transferase) and paxO (oxidoreductase)] that have demonstrated or possible functions in paxilline modification [ 11 ]. These genes were tandemly arranged in the cluster from PC-07 to PC-13 and PC-18 to PC-19, interrupted by genes PC-14 to PC-17.…”
Section: Resultsmentioning
confidence: 99%
“…Using Penicillium paxilli as a model experimental system we have identified and functionally characterized the genes required for the synthesis of paxilline [ 10 , 11 ], a potent inhibitor of calcium activated BK channels [ 7 ]. Genetic analysis of P. paxilli has established that a cluster of seven genes is required for paxilline biosynthesis [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation